The Influence of Leader-Member Exchange and Value Congruence on Job Satisfaction with Perceived Organizational Support as a Mediator - Fitriana, Anita Wahyu; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (Lembaga Penelitian Universitas YARSI, 2024)
This research aimed to examine the impact of leader-member exchange (LMX) and value congruence (VC) on job satisfaction (KK) through perceived organizational support (POS) as mediation. Conducted at PT DM Baru Retailindo Sewon Bantul, Yogyakarta, with 50 employees participating, the study employed saturated sampling and questionnaires for data collection. Data analysis utilized SPSS, encompassing classical assumption tests, multiple linear regression analysis, and the Sobel test. Findings indicate a positive influence of LMX on POS (p<0.05) and of VC on POS (p<0.05). However, LMX didn't significantly influence job satisfaction (p<0.05), while VC did (p<0.05). Interestingly, POS didn't affect KK (p>0.05). Both LMX and VC exerted significant effects on KK with POS as a mediator. Implications suggest a need for organizational enhancements, particularly in areas like LMX, to foster employee satisfaction. Providing organizational support and attention to employees facing challenges could enhance job satisfaction within the company.